Tyson's run [videorecording (DVD)] - Cochrane, Rory; Smart, Amy, 1976-; Dodson, Major; Felder, Layla; Zevallos, Claudia; Wilson, Reno; Abdi, Barkhad (Universal, 2022)
An unathletic boy with autism strives to become an unlikely marathon champion giving his unfulfilled father purpose and a second chance at putting his family first.